Biallelic deletion 13q14.3 in patients with chronic lymphocytic leukemia: Cytogenetic, FISH and clinical studies - Chena, Christian (2008)
Background and objective: Monoallelic deletion of 13q14.3 (13q14x1) is the most common abnormality in chronic lymphocytic leukemia (CLL). As a sole alteration, it predicts a favorable outcome. Biallelic 13q14.3 (13q14x2) deletion or concomitant 13q14x1/13q14x2 has been scarcely evaluated in the literature. We present the clinical, cytogenetic and fluorescence in situ hybridization (FISH) analysis of six CLL patients with normal karyotypes and 13q14x2 and their comparison to cases with 13q14x1 as a single abnormality. Patients and methods: A total of 103 CLL patients were studied. Cytogenetic and FISH analysis were performed on stimulated peripheral blood lymphocytes. Specific fluorescence DNA probes for CLL were used. Results: Six out of 103 (5.8%) patients showed normal karyotypes and 13q14x2. It was observed as a single alteration in one patient and combined with 13q14x1 in five cases. Biallelic clones were larger than monoallelic ones in 3/5 patients (60%). The comparison of clinical and hematological data between 13q14x1 and 13q14x2 groups showed progression of the disease in all 13q14x2 patients respect to 12/32 (37.5%) cases with 13q14x1 (P = 0.008), significant differences in the distribution by Rai stage (P = 0.042) and a tendency of a higher lactate dehydrogenase level in 13q14x2 patients (P = 0.054). Treatment free survival for 13q14x2 group was 28.5 months, shorter than those observed in patients with 13q14x1 alone (49 months). Conclusions: Our data would suggest that 13q14x2 could represent a more aggressive FISH anomaly than 13q14x1 alone, probably as a consequence of clonal evolution and/or due to the complete inactivation of this critical region by mean of more complex mechanisms. © 2008 The Authors.